Macrophage migration inhibitory factor is required for recruitment of scar‐associated macrophages during liver fibrosis. Issue 1 (14th November 2014) - Barnes, Mark A.; McMullen, Megan R.; Roychowdhury, Sanjoy; Madhun, Nabil Z.; Niese, Kathryn; Olman, Mitchell A.; Stavitsky, Abram B.; Bucala, Richard; Nagy, Laura E.
Abstract : A role for MIF in macrophage recruitment during progression and resolution of experimental fibrosis. Abstract : Recruitment of peripheral monocytes to the liver is a key contributor to the response to injury. MIF can act as a chemokine and cytokine, regulating innate immune responses in many tissues and cell types. We hypothesized that MIF contributes to the progression of CCl4 ‐induced hepatic fibrosis by regulating recruitment of SAM. SAMs dynamically regulate HSC activation and ECM degradation. To gain insight into the role of MIF in progression of liver fibrosis, we investigated markers of fibrosis and immune responses after chronic CCl4 administration to female C57BL/6 and MIF −/− mice. Chronic CCl4 exposure increased activation of HSC in WT mice, indicated by increased expression of α SMA mRNA and protein, as well as mRNA for collagen 1 α 1; these responses were blunted in female MIF −/− mice. Despite lower activation of HSC in MIF −/− mice, accumulation of ECM was similar in WT and MIF −/− mice, suggesting a decreased rate of ECM degradation. Recruitment of SAMs was lower in MIF −/− mice compared with WT mice, both in their initial inflammatory phenotype, as well as in the later phase as proresolution macrophages. The decreased presence of resolution macrophages was associated with lower expression of MMP13 in MIF −/− mice. Taken together, these data indicate that MIF‐dependent recruitment of SAMs contributes to degradation of ECM via MMP13, highlighting the importance of appropriate recruitment and phenotypic profile of macrophages in the resolution of fibrosis.